Commercial Tara Protein: Functional properties and use to stabilize sacha inchi oil emulsions obtained by ultrasound - Jhajaira Angelitha Sulca-Vásquez; Eliana Marcela Vélez-Erazo; José Luis Pasquel-Reátegui; Oscar Wilfredo Mendieta-Taboada (Scientia Agropecuaria)
Commercial tara protein (CTP) and sacha inchi oil are promising Peruvian products for forming food emulsions. The present work aimed (1) to characterize the functional properties of CTP as a new protein source (water and oil absorption, foam, and gelling capacity) and (2) to deepen the CTP to form sacha inchi oil emulsions. The CTP (2%, 4%, 6%) and oil concentration (15%, 20% and 25%) were evaluated for rotor-stator (RS) emulsion production. Final emulsions (RS-US) were produced with RS emulsions added with 2% tara gum and ultrasound homogenization at 75% power amplitude for 3 min. Emulsions were analyzed according to gravitational stability, droplet size, and optical microscopy. The results showed that the CTP presented a centesimal composition of 6.03% moisture, 45.16% proteins, 12.32% lipids, 2.49% fiber, 6.04% ashes, and 27.96% carbohydrates. CTP had a greater oil absorption (2.1442 ±0.26 g/g solids) than water absorption (1.8201 ±0.02 g/g solids), did not present foam formation, and the least gelation concentration was 18%. RS-US emulsions prepared with 25% oil and 2% or 4% protein had greater stability against the creaming index and phase separation during 4h, despite emulsion prepared with 15% oil presenting the lowest mean droplet size. In conclusion, the results show that commercial tara protein effectively prepared emulsions with a combined method (rotor-stator, ultrasound, and tara gum).